2013
DOI: 10.1167/13.5.25
|View full text |Cite
|
Sign up to set email alerts
|

Regional effects of clutter on human target detection performance

Abstract: Clutter is something that is encountered in everyday life, from a messy desk to a crowded street. Such clutter may interfere with our ability to search for objects in such environments, like our car keys or the person we are trying to meet. A number of computational models of clutter have been proposed and shown to work well for artificial and other simplified scene search tasks. In this paper, we correlate the performance of different models of visual clutter to human performance in a visual search task using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 28 publications
1
41
1
Order By: Relevance
“…Previous research has demonstrated an impact of visual clutter on search performance in single-target searches (e.g., Rosenholtz et al, 2007) and, more recently, within a 6 to 7 radius around a target (Asher et al, 2013). However, the current results did not demonstrate a significant effect of clutter on the low-or high-salience, single-target hit rates or response time measures.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Previous research has demonstrated an impact of visual clutter on search performance in single-target searches (e.g., Rosenholtz et al, 2007) and, more recently, within a 6 to 7 radius around a target (Asher et al, 2013). However, the current results did not demonstrate a significant effect of clutter on the low-or high-salience, single-target hit rates or response time measures.…”
Section: Discussioncontrasting
confidence: 98%
“…In the present study, we adopted the radius-specific clutter approach from Asher et al (2013) and used a simplified search array. This allowed us to define clutter purely as a function of the number of items near a target.…”
Section: Current Studymentioning
confidence: 99%
“…This finding was attributed to the smaller difference in clutter between the Neider and Zelinsky images, suggesting that Rosenholtz et al's algorithms are sensitive only to large changes in clutter. In addition, Asher et al (2013) found no significant correlation between search time and any of the metrics of Rosenholtz et al, although there were some significant correlations with true and false positive rates for subband entropy and edge density (both r = -.21, p = .02; measures were averaged per image). In this case, the authors explained the discrepancy with the fact that they used real-life images of natural scenes as opposed to maps.…”
Section: Discussionmentioning
confidence: 69%
“…In complicated intersections, people take longer to navigate and make more mistakes (Montello, 2005), while the level of visual clutter was shown to increase the time needed for finding an object in a visual scene (Asher, Tolhurst, Troscianko, & Gilchrist, 2013). In a complex situation, even if the target street can be successfully referred to a via path reference, mentioning landmarks could be truly helpful for the addressee.…”
Section: Path and Landmark Referencesmentioning
confidence: 99%
“…The excess of items and their disorganized display lead to crowding and occlusion, thus decreasing object recognition performance (Bravo & Farid, 2006) and increasing the difficulty of both segmenting a scene (Bravo & Farid, 2004) and performing visual search (Asher et al, 2013;Henderson, Chanceaux, & Smith, 2009;Neider & Zelinsky, 2011). The number of objects in a scene positively correlates with the reaction times for finding a target (Rosenholtz et al, 2007).…”
Section: Visual Cluttermentioning
confidence: 99%